1992
DOI: 10.1136/jramc-138-02-02
|View full text |Cite
|
Sign up to set email alerts
|

The Smoking Habits of Young Soldiers

Abstract: SUMMARY: In a survey of the smoking habits of over 6,000 young soldiers, it was found that the prevalence of regular smoking was 45070. Though the prevalence of regular smoking in young soldiers is higher than the general prevalence rate for smoking in 16 to 19-year olds in the civilian population, the excess is considered to be a reflection of the social and geographical background of Army recruits.The survey found that young soldiers who smoke, smoke heavily. "Eighty two percent smoked more than 20 cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
3
10
0
Order By: Relevance
“…Although the Tri-service survey conducted in 19897 was not restricted to recruits (so includes older personnel), the prevalences we report at 3-years follow-up are similar to those found in this survey. The prevalence we found amongst Army recruits is also similar to that reported by Lewthwaite and Graham for Army recruits in 198812 (45%), and our estimate at enlistment of 13% for Royal Marines corresponds directly to the published estimate 14. Apart from the RM, there were significant differences between the smoking behaviour of officers and other ranks but, even amongst officers, smoking prevalence had increased by 2002.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the Tri-service survey conducted in 19897 was not restricted to recruits (so includes older personnel), the prevalences we report at 3-years follow-up are similar to those found in this survey. The prevalence we found amongst Army recruits is also similar to that reported by Lewthwaite and Graham for Army recruits in 198812 (45%), and our estimate at enlistment of 13% for Royal Marines corresponds directly to the published estimate 14. Apart from the RM, there were significant differences between the smoking behaviour of officers and other ranks but, even amongst officers, smoking prevalence had increased by 2002.…”
Section: Discussionsupporting
confidence: 90%
“…Although the rates of smoking reported were very high, there was a clear reduction in recruits smoking over this time period. When the survey was repeated in 1988, the prevalence of regular smoking amongst young soldiers was found to be 45% 12. More recent collection of lifestyle data on a small sample of Army recruits found that 40% were current smokers and 11% were ex-smokers 13.…”
Section: Introductionmentioning
confidence: 99%
“…Ex-smokers were most likely to cite fitness and health as a reason for quitting,22 suggesting a positive impact of the mandatory cardiorespiratory fitness testing programme which had been introduced in the late 1970s. It is likely that wider societal trends in smoking were also contributory, although military smoking remained higher 5. Smoking cessation support including brief intervention, nicotine replacement and pharmacological intervention is now routinely embedded in Defence Primary Care 23.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of military smoking has reduced over time, although it has remained higher than in the civilian population 5. Possible reasons include the implementation of health-promotion policies initially introduced in the early 1960s6 and the introduction of mandatory fitness testing from the late 1970s, against a background of the falling prevalence of smoking in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Military personnel may be at increased risk of tuberculosis as a result of shared accommodation,6 increased prevalence of smoking,7 8 alcohol consumption9 or as a result of military service in high-risk areas. In the late 19th century, tuberculosis was a major cause of manpower loss, accounting for around 17% of medical discharges from the British Army in 1891 (300 per 100 000 strength per year), and was the most common disease-related cause of discharge from service.…”
Section: Introductionmentioning
confidence: 99%